2016
DOI: 10.1080/02763893.2016.1162255
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness in Assisted Living: Challenges for Quality of Life and Care

Abstract: An unknown number of mentally ill elders in the U.S. receive care in assisted living [AL], along with persons facing physical or cognitive challenges. While dementia is familiar in AL, our data indicate that neither staff nor residents are prepared to work or live with the mentally ill. Challenges are created for professionals, since these residents bring diverse needs. Daily inter-resident interactions are also disrupted or stressful. Qualitative data describe the impacts on quality of resident life as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…12 , 15 , 39 Although depression is also considered to be an aspect of the aging process and is, therefore, generally not assessed in geriatric populations, 40 the current best practice in the management of depression in AL residents is based on early screening and treatment. 9 , 41 In Jordan and in the Middle East more widely, a stigma associated with mental illness is evident. 42 In assisted living situations, health care providers do not screen for symptoms associated with depression, restricting their attention to physical illnesses, since this is considered more appropriate for the aged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 , 15 , 39 Although depression is also considered to be an aspect of the aging process and is, therefore, generally not assessed in geriatric populations, 40 the current best practice in the management of depression in AL residents is based on early screening and treatment. 9 , 41 In Jordan and in the Middle East more widely, a stigma associated with mental illness is evident. 42 In assisted living situations, health care providers do not screen for symptoms associated with depression, restricting their attention to physical illnesses, since this is considered more appropriate for the aged.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Previous research has found that residents in assisted care facilities suffering from depressive symptoms experience frustration with their careers’ limited abilities to effectively deal with depression. 9 , 45 Therefore, an interdisciplinary approach to raise awareness among staff for early recognition of the symptoms of depression among AL residents is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…They are also more likely to receive inadequate, insufficient, and inappropriate care, due to a lack of mental health services and professionals specialized in aging, lack of aging services (e.g. residential or end-of-life care) prepared for mental illness, and ageist attitudes among service providers (Clifton et al, 2013;Cummings & Kropf, 2011;Morgan, Perez, Frankowski, Nemec, & Bennett, 2016). Aging also affects mental illness diagnoses and treatment when symptoms (e.g.…”
Section: Service Accessmentioning
confidence: 99%
“…As aging patients with mental illness face increased care needs (Clifton et al,2013;Yu et al, 2015), targeted programs and interventions are required to address specific challenges associated with aging and mental health (Mueser et al, 2010). However, aging patients with mental illness are more likely to receive inadequate, insufficient, and inappropriate support due to a lack of appropriate, specialized, non-discriminatory services, and a lack of responses to specific aging and mental illness needs by government institutions, policy makers, and service providers (Clifton et al, 2013;Cummings & Kropf, 2011;Morgan et al, 2016).…”
Section: Rationales For Studying Aging Among Patients With Mental Illmentioning
confidence: 99%
“…For personal comfort and due to limited medical resources, most of them live alone within their own house instead of nursing houses [1]. However, in their private space, emergency situations may not be noticed by others in time.…”
Section: Introductionmentioning
confidence: 99%